(untitled) (Nordic Journal of Practical Theology, 2022)
The article explores and discusses how Norwegian church pastors have experienced and dealt with the role of spiritual leader in a Christian community after a predecessor had to quit because of accusations of sexually abusive behaviour. ‘Afterpastor’ is the term applied to such pastors in the United States after they discovered as a group that shared similar challenges in this role. Six pastors from four denominations in Norway are interviewed about their experiences. The resulting analysis is discussed considering theoretical perspectives on congregations as an arena for sexual violence, and literature presenting systematized practice experiences of ‘afterpastor’ role in the United States. The findings shed light on the experiences of being a pastor in a community in crisis, where both the church leadership and congregation expect the pastor to deal with the situation. The challenge seems to be limited access to sufficient resources and competent support. The need for supervision and support for pastors to address different needs are preconditions for a responsible and constructive approach to caring for themselves, those involved and the Christian community.